Evolutionary Patterns of RNA-Based Duplication in Non-Mammalian Chordates - Chen, Ming (Public Library of Science, 2011)
The role of RNA-based duplication, or retroposition, in the evolution of new gene functions in mammals, plants, and Drosophila has been widely reported. However, little is known about RNA-based duplication in non-mammalian chordates. In this study, we screened ten non-mammalian chordate genomes for retrocopies and investigated their evolutionary patterns. We identified numerous retrocopies in these species. Examination of the age distribution of these retrocopies revealed no burst of young retrocopies in ancient chordate species. Upon comparing these non-mammalian chordate species to the mammalian species, we observed that a larger fraction of the non-mammalian retrocopies was under strong evolutionary constraints than mammalian retrocopies are, as evidenced by signals of purifying selection and expression profiles. For the Western clawed frog, Medaka, and Sea squirt, many retrogenes have evolved gonad and brain expression patterns, similar to what was observed in human. Testing of retrogene movement in the Medaka genome, where the nascent sex chrosomes have been well assembled, did not reveal any significant gene movement. Taken together, our analyses demonstrate that RNA-based duplication generates many functional genes and can make a significant contribution to the evolution of non-mammalian genomes.